Air-stable glassy metal-organic framework electrolyte material and preparation method thereof

Through the preparation method of glass metal-organic frame materials, the problem of instability of solid electrolytes in the air is solved, high ionic conductivity and chemical electrochemical stability are achieved, and the safety and processability of the battery are improved, which is suitable for different Battery production in shape and size.

CN119297419APending Publication Date: 2025-01-10UNIV OF SCI & TECH LIAONING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456577.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing solid electrolytes of oxides, halides and sulfides are unstable in the air, resulting in deterioration, decomposition and release of toxic gases, limiting the industrial production and transportation of solid batteries, and lacking air-stable materials with high ionic conductivity.

Method used

Using glassy metal-organic frame material, it is mixed with binder and solvent after heat treatment in an inert gas to form a slurry, and then dried at a vacuum high temperature to make a solid electrolyte membrane for battery assembly to ensure the material Air stability and high ionic conductivity.

Benefits of technology

It achieves high ionic conductivity, mechanical strength and chemical electrochemical stability, reduces lithium dendrites' growth and interface impedance, improves the safety and processability of batteries, and is suitable for battery production of different shapes and sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297419A_ABST
    Figure CN119297419A_ABST
Patent Text Reader

Abstract

The invention discloses an air-stable glassy metal organic framework electrolyte material and a preparation method thereof, and relates to the technical field of solid electrolyte materials.The preparation method comprises the following steps that synthesized crystalline MOFs are placed in a furnace body filled with inert gas, heat treatment is conducted, and a glassy metal-organic framework is obtained; according to the air-stable glass-state metal organic framework electrolyte material and the preparation method thereof, the air-stable glass-state metal organic framework electrolyte material has the characteristics of no grain boundary and isotropy, so that high ionic conductivity is provided, meanwhile, the air-stable glass-state metal organic framework electrolyte material shows mechanical strength higher than that of a traditional polymer electrolyte, growth of lithium dendrites can be effectively inhibited, and the service life of the air-stable glass-state metal organic framework electrolyte material is prolonged. The material has good interface compatibility with a positive electrode material and a negative electrode material, can reduce interface impedance, shows excellent chemical and electrochemical stability in air and electrochemical environments, is simple in preparation process, low in cost, easy to process into different shapes and sizes, non-flammable and free of leakage risk, and improves the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte materials, in particular to air-stable glassy metal organic framework electrolyte materials and preparation methods thereof. Background Art

[0002] Solid electrolytes can directly match high-voltage positive electrodes to improve battery energy density, and have excellent dendrite growth inhibition capabilities to prevent short circuits and improve battery safety. Researchers have been seeking solid electrolytes with high ionic conductivity, but have ignored the key factor related to the industrialization of solid electrolytes—air stability. At present, although the oxide, halide, and sulfide solid electrolytes reported in research have excellent room temperature ionic conductivity, oxide solid electrolytes will deteriorate after being left in the air for a long time, reacting with carbon dioxide in the air to form lithium carbonate; sulfides will violently decompose and fail when in contact with air and release toxic gas hydrogen sulfide; halide solid electrolytes will decompose when encountering moisture in the air. These air-sensitive solid electrolytes are not conducive to the large-scale production, transportation, and storage of solid-state batteries, and are a major problem that plagues the development of solid-state batteries. Therefore, the development of air-stable solid electrolytes with suitable ionic conductivity has become a top priority for the development of solid-state batteries.

[0003] Metal-organic framework (MOFs) glass has the characteristics of no grain boundaries and isotropy, which can ensure efficient ion conduction; at the same time, glassy metal-organic frameworks have excellent air stability and low price. These characteristics make glassy metal-organic framework solid electrolytes quite advantageous and competitive compared to oxide, halide, and sulfide solid electrolytes, and are electrolyte materials with great industrialization potential. To this end, we propose air-stable glassy metal-organic framework electrolyte materials and preparation methods. Summary of the invention

[0004] The object of the present invention is to provide an air-stable glassy metal organic framework electrolyte material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: an air-stable glassy metal organic framework electrolyte material and a preparation method, comprising the following steps:

[0006] S1: placing the synthesized crystalline MOFs in a furnace filled with inert gas and performing heat treatment to obtain a glassy metal-organic framework;

[0007] S2: grinding the glassy MOFs obtained in step S1, wherein the glassy MOFs matrix can conduct cations, and mixing with a certain amount of binder and solvent to obtain a slurry;

[0008] S3: coating the slurry obtained in step S2 on the diaphragm, drying it under vacuum and at high temperature, and then cutting it into a solid electrolyte membrane of a desired size;

[0009] S4: Assemble button-type, soft-pack, cylindrical or square-shell batteries with the glassy MOF-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, solid electrolyte and positive electrode.

[0010] Preferably, the MOFs in S1 include but are not limited to one or more of phosphate-imidazole series, zeolite imidazole salt series, thiocyanate, fluorosulfonyl imide-nitrile framework series, metal-bisacetamide framework, carboxylic acid metal-organic framework and pyridine-carboxylic acid metal-organic framework.

[0011] Preferably, in S1, the heat treatment heating rate is 1-20°C / min, the heat treatment temperature is 100-600°C, and the time is 1-180min.

[0012] Preferably, in S2, the mass ratio of glassy MOFs to binder is 9-6:0.5-4.

[0013] Preferably, in S3, the thickness of the solid electrolyte membrane is 20 to 120 μm, the vacuum drying temperature is 40° C. to 150° C., and the time is 4 to 12 hours.

[0014] Preferably, in S3, the vacuum-dried MOFs powder is subjected to pressure or coating to prepare the MOFs powder into a MOFs film or a MOFs sheet.

[0015] Preferably, in the S2, the conductive cations include any one of Li ions, Na ions, Mg ions, Ca ions, Al ions, K ions, Zn ions, and protons.

[0016] Preferably, in S2, the binder is a water-based binder and the oily binder is PVDF.

[0017] Preferably, the conductive cation is a Li ion, and the solid-state lithium battery is a solid-state battery whose carrier is a Li ion;

[0018] When the cation is Na ion, it can be a solid-state sodium battery;

[0019] When the cation is Mg ion, it can be a solid-state magnesium battery;

[0020] When the cation is a Ca ion, it can be a solid calcium battery;

[0021] When the cation is K ion, it can be a solid-state potassium battery;

[0022] When the cation is Zn ion, it can be a solid-state zinc battery;

[0023] When the cation is Al ion, it can be a solid aluminum battery;

[0024] When the cation is a proton, it can be a solid-state fuel cell.

[0025] Preferably, in S4, the positive electrode, the negative electrode and a solid electrolyte between the positive electrode and the negative electrode are arranged and assembled, and the solid electrolyte is a glassy metal-organic framework solid electrolyte.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention provides high ionic conductivity due to its grain boundary-free and isotropic properties through the preparation method, and at the same time exhibits higher mechanical strength than traditional polymer electrolytes, and can effectively inhibit the growth of lithium dendrites. This material has good interface compatibility with positive and negative electrode materials, can reduce interface impedance, and exhibits excellent chemical and electrochemical stability in air and electrochemical environments. The preparation process is simple, low cost, easy to process into different shapes and sizes, non-flammable and has no leakage risk, thereby improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The air stability XRD diagram of the glassy metal-organic framework solid electrolyte prepared by the present invention;

[0029] Figure 2 This is a constant current charge and discharge performance diagram of the air-stable glassy metal-organic framework solid electrolyte prepared by the present invention under the conditions of 25°C and 1C. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1: The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method, comprising the following steps:

[0032] S1, placing the synthesized crystalline ZIF-7 in a furnace filled with inert gas, heating it to 400°C at a rate of 2°C / min, keeping it at that temperature for 5 minutes, and then melting and quenching to obtain glassy ZIF-7;

[0033] S2. Grind the glassy ZIF-7 obtained in step S1, mix the powder and the binder in a ratio of 9:1, add 1 ml of solvent, and mix for 15 minutes to obtain a slurry.

[0034] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 8 μm, dried at 60° C. in vacuum for 6 h, and then cut into solid electrolytes of required size.

[0035] S4, assembling a battery with the glassy ZIF-7-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0036] Test method: Take any glassy ZIF-7-based solid electrolyte prepared in Example 1, soak it with an electrolyte containing lithium salt, and use XRD to determine the phase after exposing it to air for 30 days. Figure 1 ; Then the battery was assembled after vacuum drying at 80℃ for 4h, and the constant current charge and discharge performance test was performed.

[0037] The electrochemical performance of the glassy ZIF-7-based solid electrolyte of Example 1 in the air stability test measured by the above method is as follows: Figure 2 shown.

[0038] Example 2

[0039] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0040] S1. The synthesized crystalline ZIF-76 is placed in a furnace filled with inert gas, heated to 420°C at a rate of 10°C / min, kept at this temperature for 30 minutes, and then melted and quenched to obtain glassy ZIF-76;

[0041] S2. Grind the glassy ZIF-76 obtained in step S1, mix the powder and the binder in a ratio of 6:4, add 2 ml of solvent, and mix for 30 minutes to obtain a slurry.

[0042] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 12 μm, dried at 60° C. in vacuum for 8 h, and then cut into solid electrolytes of required size.

[0043] S4, assembling a battery with the glassy ZIF-76-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0044] Take any glassy ZIF-76-based solid electrolyte prepared in Example 2, soak it with an electrolyte containing a lithium salt, and then assemble the battery after drying at 80° C. in vacuum for 4 h, and perform a constant current charge and discharge performance test.

[0045] Example 3

[0046] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0047] S1, placing the synthesized ZIF-UC-5 in a furnace filled with inert gas, heating it to 470°C at 5°C / min, keeping it at that temperature for 60min, and then melting and quenching to obtain glassy ZIF-UC-5;

[0048] S2. Grind the glassy ZIF-UC-5 obtained in step S1, mix the powder and the binder in a ratio of 7:3, add 1.5 ml of NMP solvent, and mix for 40 minutes to obtain a slurry.

[0049] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 15 μm, dried at 70° C. in vacuum for 5 h, and then cut into solid electrolytes of required size.

[0050] S4, assembling a battery with the glassy ZIF-UC-5-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0051] Test method: Take any glassy ZIF-UC-5-based solid electrolyte prepared in Example 3, soak it with an electrolyte containing a lithium salt, and then assemble the battery after drying at 80°C in vacuum for 4 hours, and perform a constant current charge and discharge performance test.

[0052] Example 4

[0053] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0054] S1. The synthesized crystalline ZIF-92 is placed in a furnace filled with inert gas, heated to 480°C at 8°C / min, kept at this temperature for 45 minutes, and then melted and quenched to obtain glassy ZIF-92;

[0055] S2. Grind the glassy ZIF-92 obtained in step S1, mix the powder and the binder in a ratio of 8:2, add 2.5 ml of solvent, and mix for 15 minutes to obtain a slurry.

[0056] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 18 μm, dried at 80° C. in vacuum for 4 h, and then cut into solid electrolytes of required size.

[0057] S4, assembling a battery with the glassy ZIF-92-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0058] Test method: Take any glassy ZIF-92-based solid electrolyte prepared in Example 4, soak it with an electrolyte containing a lithium salt, and then assemble the battery after drying it at 80°C in vacuum for 4 hours, and perform a constant current charge and discharge performance test.

[0059] Example 5

[0060] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0061] S1. The synthesized crystalline [Zn3(H2PO4)6(H2O)3](BTA) was placed in a furnace filled with inert gas, heated to 150°C at a rate of 10°C / min, kept at that temperature for 50 min, and then melted and quenched to obtain glassy ZIF-UC-6;

[0062] S2. Grind the glassy [Zn3(H2PO4)6(H2O)3](BTA) obtained in step S1, mix the powder and the binder in a ratio of 8:2, add 3 ml of solvent, and mix for 20 minutes to obtain a slurry.

[0063] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 20 μm, and then dried at 70° C. in vacuum for 10 h and cut into solid electrolytes of required size.

[0064] S4. Assemble the battery with the glassy [Zn3(H2PO4)6(H2O)3](BTA)-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, glassy metal-organic framework solid electrolyte membrane and positive electrode.

[0065] Test method: Take any [Zn3(H2PO4)6(H2O)3](BTA)-based solid electrolyte prepared in Example 5, infiltrate it with an electrolyte containing a lithium salt, and then assemble the battery after drying it at 80°C in vacuum for 4 hours, and perform a constant current charge and discharge performance test.

[0066] Example 6

[0067] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0068] S1. The synthesized crystalline UiO-67 is placed in a furnace filled with inert gas, heated to 200°C at a rate of 10°C / min, kept at this temperature for 45 minutes, and then melt-quenched to obtain glassy UiO-67;

[0069] S2. Grind the glassy UiO-67 obtained in step S1, mix the powder and the binder in a ratio of 8:2, add 3 ml of solvent, and mix for 20 minutes to obtain a slurry.

[0070] S3. The slurry obtained in step S2 is coated on the diaphragm with a thickness of 22 μm, dried at 85° C. in vacuum for 4 h, and then cut into solid electrolytes of required size.

[0071] S4, assembling a battery with the glassy UiO-678-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0072] Test method: Take any glassy UiO-67-based solid electrolyte prepared in Example 6, infiltrate it with an electrolyte containing a lithium salt, and then assemble the battery after drying at 80°C in vacuum for 4 hours, and perform a constant current charge and discharge performance test.

[0073] Example 7

[0074] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0075] S1. The synthesized crystalline Cu2(SCN)3(C4bpy) was placed in a furnace filled with inert gas, heated to 480°C at 12°C / min, kept at this temperature for 45 min, and then melted and quenched to obtain glassy ZIF-62;

[0076] S2. Grind the glassy Cu2(SCN)3(C4bpy) obtained in step S1, mix the powder and the binder in a ratio of 6:4, add 2.5 ml of solvent, and mix for 10 minutes to obtain a slurry.

[0077] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 13 μm, dried at 80° C. in vacuum for 4 h, and then cut into solid electrolytes of required size.

[0078] S4. Assemble the battery with the glassy Cu2(SCN)3(C4bpy)-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane and the positive electrode.

[0079] Test method: Take any glassy Cu2(SCN)3(C4bpy)-based solid electrolyte prepared in Example 7, soak it with an electrolyte containing a lithium salt, and then assemble the battery after drying it at 80°C in vacuum for 4 hours, and perform a constant current charge and discharge performance test.

[0080] Example 8

[0081] The present invention provides a technical solution: an air-stable glassy metal-organic framework electrolyte material and a preparation method thereof, comprising the following steps:

[0082] S1, synthesized crystalline Ti 12 O 16 (O-iPr) 16 Place it in a furnace filled with inert gas, heat it to 250°C at 14°C / min, keep it warm for 40 minutes, then melt and quench to obtain glassy Ti 12 O 16 (O-iPr) 16 ;

[0083] S2, the glassy Ti obtained in step S1 12 O 16 (O-iPr) 16 After grinding, the powder and the binder were evenly mixed in a ratio of 8:2, and 2 ml of solvent was added. After mixing for 12 minutes, a slurry was obtained.

[0084] S3. The slurry obtained in step S2 is coated on the separator with a thickness of 25 μm, dried at 85° C. in vacuum for 5 h, and then cut into solid electrolytes of required size.

[0085] S4, the glassy Ti obtained in step S3 12 O 16 (O-iPr) 16 The battery is assembled according to the structural layout of the negative electrode, the glassy metal-organic framework solid electrolyte membrane, and the positive electrode.

[0086] Test method: Take any glassy Ti prepared in Example 8 12 O 16 (O-iPr) 16 The solid-state electrolyte was prepared by soaking it with an electrolyte containing a lithium salt, and then the battery was assembled after being dried at 80°C in vacuum for 4 hours, and the constant current charge and discharge performance was tested.

Claims

1. A method for preparing an air-stable glassy metal-organic framework electrolyte material, characterized in that: The following steps are involved: S1: placing the synthesized crystalline MOFs in a furnace filled with inert gas and performing heat treatment to obtain a glassy metal-organic framework; S2: grinding the glassy MOFs obtained in step S1, and mixing them with a certain amount of binder and solvent to obtain a slurry; S3: coating the slurry obtained in step S2 on the diaphragm, drying it under vacuum and at high temperature, and then cutting it into a solid electrolyte membrane of a desired size; S4: Assemble button-type, soft-pack, cylindrical or square-shell batteries with the glassy MOF-based solid electrolyte membrane obtained in step S3 according to the structural layout of the negative electrode, solid electrolyte and positive electrode.

2. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: The MOFs in S1 include but are not limited to phosphate-imidazole series (such as [Zn(HPO4)(H2PO4)](H2Im)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3]H(2-MebIm), [Zn3(H2PO4)6(H2O)3](BTA) etc.), zeolite imidazole salt series (such as ZIF-7, ZIF-8, ZIF-62, ZIF-76 etc.), titanyl-hydroquinone series (such as Ti 16 O 16 (OEt) 32 、Ti 12 O 16 (O-iPr) 16 etc.), thiocyanates (such as Cu2(SCN)3(C4bpy), [Co(μ-NCS)2(C5H5N3O)2]·C5H5N3O) and bis(fluorosulfonyl)imide-nitrile framework series (such as Li[N(SO2F)2](NCCH2CH2CN)2), metal-bis(acetamide) framework (such as Co(hmba)3[Co(NCS)4], Co(bba)3[CoCl4], Co(hmba)3[CoBr4]), carboxylic acid metal-organic framework (such as UiO-67, UiO-68, DUT-5, [Mg4(adipate)4(DMA)(H2O),) pyridine-carboxylic acid metal-organic framework (such as [Mn3(peb)6]·2DMF) or at least one of them.

3. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: In S1, the heat treatment heating rate is 1-20°C / min, the heat treatment temperature is 100-600°C, and the time is 1-180min.

4. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: In the S2, the mass ratio of glassy MOFs to binder is 9-6:0.5-4.

5. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: In the step S3, the thickness of the solid electrolyte membrane is 20 to 120 μm, the vacuum drying temperature is 40° C. to 150° C., and the time is 4 to 12 hours.

6. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: In S3, the vacuum-dried MOFs powder is subjected to pressure or coating to prepare a MOFs film or a MOFs sheet.

7. The method for preparing the air-stable glassy metal-organic framework electrolyte material according to claim 1, characterized in that: In the S2, the conductive cations include any one of Li ions, Na ions, Mg ions, Ca ions, Al ions, K ions, Zn ions, and protons.

8. The method for preparing the air-stable glassy metal organic framework electrolyte material according to claim 1, characterized in that: In S2, the binder includes but is not limited to a water-based binder and an oil-based binder.

9. The air-stable glassy metal organic framework electrolyte material and preparation method according to claim 7, characterized in that: The conductive cation is Li ion, which is a solid-state lithium battery. The solid-state lithium battery is a solid-state battery whose carrier is Li ion; When the cation is Na ion, it can be a solid-state sodium battery; When the cation is Mg ion, it can be a solid-state magnesium battery; When the cation is a Ca ion, it can be a solid calcium battery; When the cation is K ion, it can be a solid-state potassium battery; When the cation is Zn ion, it can be a solid-state zinc battery; When the cation is Al ion, it can be a solid aluminum battery; When the cation is a proton, it can be a solid-state fuel cell.

10. Air-stable glassy metal-organic framework electrolyte material, characterized in that: In S4, the positive electrode, the negative electrode and the solid electrolyte between the positive electrode and the negative electrode are arranged and assembled, and the solid electrolyte is a glassy metal-organic framework solid electrolyte.